PIEZO2‐related distal arthrogryposis type 5: Longitudinal follow‐up of a three‐generation family broadens phenotypic spectrum, complications, and health surveillance recommendations for this patient group. Issue 9 (14th June 2022) - Sherlaw‐Sturrock, Charlotte A.; Willis, Tracey; Kiely, Nigel; Houge, Gunnar; Vogt, Julie
Abstract: Arthrogryposis is a heterogenous condition with a wide variety of etiological causes. It has been subdivided clinically based on the presence of additional features. Dominant gain of function (GoF) pathogenic variants in PIEZO2 have been associated with several forms of arthrogryposis. Previous reports have focused on diagnosis and clinical features. We report a three‐generation family with four affected individuals with a known pathogenic GoF change p.(Glu2727del) in PIEZO2 . All family members presented at birth with distal arthrogryposis and ophthalmoplegia but have varied in their subsequent clinical course with differences in mobility and joint restriction. In the longer term, other features have presented including dysphagia, back pain and spinal stenosis‐like symptoms, raised intraocular pressure, and progressive restrictive lung disease. As far as we know, this is the first report detailing the longitudinal follow‐up of a three‐generation family which highlights potential long‐term complications in patients with PIEZO2 ‐related arthrogryposis. We present this family to demonstrate the importance of long‐term follow‐up for the clinical management of this group of patients.